Population pharmacokinetics of olprinone in healthy male volunteers - Kunisawa T; Kasai H; Suda M; Yoshimura M; Sugawara A; Izumi Y; Iida T; Kurosawa A; Iwasaki H (Dove Medical Press, 2014)
Takayuki Kunisawa,1 Hidefumi Kasai,2 Makoto Suda,2 Manabu Yoshimura,3 Ami Sugawara,3 Yuki Izumi,3 Takafumi Iida,3 Atsushi Kurosawa,3 Hiroshi Iwasaki3 1Surgical Operation Department, Asahikawa Medical University Hospital, Hokkaido, Japan; 2Clinical Study Management Division, Bell Medical Solutions Inc, Tokyo, Japan; 3Department of Anesthesiology and Critical Care Medicine, Asahikawa Medical University, Hokkaido, Japan Background: Olprinone decreases the cardiac preload and/or afterload because of its vasodilatory effect and increases myocardial contractility by inhibiting phosphodiesterase III. Purpose: The objective of this study was to characterize the population pharmacokinetics of olprinone after a single continuous infusion in healthy male volunteers. Methods: We used 500 plasma concentration data points collected from nine healthy male volunteers for the study. The population pharmacokinetic analysis was performed using the nonlinear mixed effect model (NONMEM®) software. Results: The time course of plasma concentration of olprinone was best described using a two-compartment model. The final pharmacokinetic parameters were total clearance (7.37 mL/minute/kg), distribution volume of the central compartment (134 mL/kg), intercompartmental clearance (7.75 mL/minute/kg), and distribution volume of the peripheral compartment (275 mL/kg). The interindividual variability in the total clearance was 12.4%, and the residual error variability (exponential and additive) were 22.2% and 0.129 (standard deviation). The final pharmacokinetic model was assessed using a bootstrap method and visual predictive check. Conclusion: We developed a population pharmacokinetic model of olprinone in healthy male adults. The bootstrap method and visual predictive check showed that this model was appropriate. Our results might be used to develop the population pharmacokinetic model in patients. Keywords: phosphodiesterase III inhibitor, men, pharmacokinetic model